Allocation of Carbon Emission Permits among Industrial Sectors in Liaoning Province. (December 2016) - Mu, Hailin; Li, Linlin; Li, Nan; Xue, Zhaoquan; Li, Longxi
Abstract: China will establish its national ETS to reduce carbon emissions gradually. A reasonable CO2 emissions allocation method helps to stimulate the emitters actively at the beginning stage. The paper takes industrial sectors of Liaoning province as a case to distribute the carbon emission permits. Considering the principles of fairness and efficiency, it analyzes the distribution of carbon emission permits among sectors in detail based on the method of CRITIC and fuzzy optimization model. The final allocation proportions are profitable to build the future carbon trading market in Liaoning province and provide reference for policy makers.